Optimizing Student Admission Process Through EPPMB - Raemon Syaljumairi; Ervan Asri; Sarmiadi (Ikatan Ahli Informatika Indonesia Nusantara, 2024)
The research addresses the challenges of managing multiple admission channels in higher education institutions through a comprehensive web-based solution. Following Design Science Research Methodology, we developed and implemented a multi-layer architecture that integrates various admission processes while maintaining system security and performance. The system handles six distinct admission channels, including Recognition of Prior Learning (RPL), Applied Master's Program, and industry partnership programs. Results demonstrate significant improvements in operational efficiency, with a 65% reduction in application processing time and error rates below 0.1%.